Experimental investigation of profile eye shape on plate bending: The role of rotational speed - Mustaza Ma'a; Prawira Yuda; Novison Roni; Yanda Zaira Jupri (JTTM : Jurnal Terapan Teknik Mesin, 2025)
The bending of profile plates is a critical process in various engineering applications, including automotive, aerospace, and shipbuilding industries. In simple circumstances, this profile plate bending machine is intended to make pan profiles and mosque dome profiles. This process’s precision and efficiency significantly impact the final product’s structural integrity and performance. Traditional methods of plate bending often face challenges such as uneven stress distribution, material deformation, and inefficiencies in production time. Recent advancements in mechanical engineering have highlighted the importance of understanding the factors that influence plate bending. Among these factors, the rotational speed affects the dynamic forces applied during the bending process, which influences the degree of deformation and the quality of the bend. Similarly, the profile eye shape determines the plate’s contact area and stress distribution, impacting the bending outcome. Although these factors are recognized as important, there is a lack of comprehensive experimental studies that systematically investigate their combined effect on plate bending. This research aims to fill this gap by investigating how varying rotational speeds and different profile eye shapes affect the bending of profile plates. Understanding these relationships, can optimize the bending process, improve product quality, and enhance manufacturing efficiency. This study will provide valuable insights for engineers and manufacturers, enabling them to make informed decisions about the design and operation of bending equipment. Ultimately, this research will contribute to developing more efficient and precise bending techniques, benefiting a wide range of industrial applications.